Menjelaskan Adopsi Aplikasi Shopee Menggunakan Technology Acceptance Model Davis 1985 - Christopher, Eric (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The use of online shopping applications has spread widely at present. However, the reasons why consumers use these applications are not fully understood. Therefore, by adapting the Technology Acceptance Model, this study aims to find the factors that encourage online shoppers to use the Shopee application. The three exogenous variables are perceived complexity, self-efficacy, and internet connection. The sample data is 150 respondents, taken by judgment sampling and processed using structural equation modelling with WarpPLS. This study found that complexity does not have a direct effect on perceived usefulness but has a negative influence on perceived ease of use. As hypothesised, self-efficacy determines perceived usefulness and perceived ease of use positively and significantly. The impact of internet connection on perceived usability and perceived ease of use are also in the same pattern. The same result was also performed by perceived ease of use on perceived usefulness and attitudes toward the use and perceived usefulness on attitudes toward use. Future research can add anticipated emotions as an exogenous variable.